Factors Affecting the Prevalence of Online Sexual Abuse and Exploitation of Children in Camarines Sur, Bicol Region, Philippines - Sales, Ma. Vida Teresa; Uclaray, Angelo; Baldoza, Russ Daniel; Niñofranco, Joselynn; Dycoco, Cherry; Añonuevo, Tania; Pereyra, Myrna (Asean Social Work Journal, 2023)
The culture within the family and community generally affects people's attitudes and acceptance towards using available technology. Alternately, technology can also influence the culture and social behaviors of people. This study aimed to discuss the family and community factors and their unintentional contribution to the prevalence of Online Sexual Abuse and Exploitation of Children (OSAEC) and explore the community's perspectives of OSAEC. Utilizing a qualitative approach, it employed focus group discussions and interviews to obtain relevant data and insights from the participants. Based on thematic analysis, family factors include (1) unsupervised access to the internet and gadgets, (2) children disregarding their parents' reminders on gadget usage, and (3) parents' lack of knowledge on the use of phones and the internet. In terms of community factors, (1) poor socioeconomic conditions, (2) limited community initiatives to capacitate parents on online media risks and OSAEC, and (3) limited knowledge of emerging child protection issues may have contributed to OSAEC cases. Furthermore, the study found that community members view OSAEC as a cybercrime involving showing and sending obscene pictures, texts, or videos without physical contact. Given the findings, establishing appropriate mechanisms for responsible online use and online behavior is vital to ensure proactiveness in protecting children against abuse and exploitation at family and community levels